2019
DOI: 10.1016/j.ejmech.2019.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Acylated sulfonamide adenosines as potent inhibitors of the adenylate-forming enzyme superfamily

Abstract: The superfamily of adenylate-forming enzymes all share a common chemistry. They activate a carboxylate group, on a specific substrate, by catalyzing the formation of a high energy mixed phosphoanhydride-linked nucleoside intermediate. Members of this diverse enzymatic family play key roles in a variety of metabolic pathways and therefore many have been regarded as drug targets. A generic approach to inhibit such enzymes is the use of non-hydrolysable sulfur-based bioisosteres of the adenylate intermediate. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…For all three ligand-bound structures the calculated electron density map permitted unambiguous modelling of compounds 5a-5c (Supplementary Figure 4A). Comparison of the seryl, sulfamoyl and ribose moieties in the three ligandbound structures shows that they make the same interactions as observed in the previously published structure of Kp-serRS in complex with SSA 27 (Supplementary Figures 3B and 4B). Therefore, the relative affinity of the pyrimidine-containing compounds can be solely attributed to base-protein interactions (Figure 3A).…”
Section: X-ray Crystal Structures Reveal Basis Of Pyrimidine Selectivitysupporting
confidence: 75%
See 2 more Smart Citations
“…For all three ligand-bound structures the calculated electron density map permitted unambiguous modelling of compounds 5a-5c (Supplementary Figure 4A). Comparison of the seryl, sulfamoyl and ribose moieties in the three ligandbound structures shows that they make the same interactions as observed in the previously published structure of Kp-serRS in complex with SSA 27 (Supplementary Figures 3B and 4B). Therefore, the relative affinity of the pyrimidine-containing compounds can be solely attributed to base-protein interactions (Figure 3A).…”
Section: X-ray Crystal Structures Reveal Basis Of Pyrimidine Selectivitysupporting
confidence: 75%
“…We opted for the stable acylated sulfamate linkage as a bioisoster for the acylphosphate where nature opted for the phosphoramidate as in McC 13 . The adenine-containing variants of such compounds have been shown to be potent inhibitors with a Ki app of 0.18 nM and 0.052 nM for serRS and aspRS, respectively and therefore act as a benchmark to compare activity 26,27 .…”
Section: Evaluation Of Inhibitory Activity Of Albomycin and MCC Cmc Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the majority of these aaSoA congeners are not able to efficiently inhibit their target aaRS. Subsequently, we substituted 5 -oxygen with a carbon atom to generate two similar isosteres [153] (aaSoHA, Figure 10a) targeting class I IleRS and class II SerRS, respectively. Evaluation of their in vitro enzyme inhibitory activity showed that the isoleucyl-sulfonamide analog retained its potency compared to the parent sulfamoyl derivative (ISA), while an almost complete loss of activity was observed for the seryl congener.…”
Section: Synthetic Bi-substrate Aars Inhibitorsmentioning
confidence: 99%
“…There are many examples of homo-multifunctional substrates that are modified using biocatalytic approaches, such as polyhydroxy [117][118][119][120][121][122][123][124][125][126][127][128], polycarboxylic [129][130][131], and polyamine Effect of the product inhibition on the reaction courses using two hypothetic enzymes, one with a very high initial activity but showing a strong inhibition by the product, the other with a lower activity but without product inhibition.…”
Section: Modification Of Multifunctional Substratesmentioning
confidence: 99%